Chronic Spontaneous Urticaria and Type 1 Diabetes Mellitus—Does Quality of Life Impairment Always Reflect Health Danger? - Brzoza, Zenon (J Clin Med, 2020)
Background and aims: Chronic spontaneous urticaria (CSU) and diabetes mellitus type 1 (T1DM) may compromise the quality of life (QoL). We decided to compare the QoL of T1DM patients to those suffering from CSU. Materials and methods: Sixty-six patients with well-controlled T1DM (male 52%) in the mean age of (SD) 36.3 (11.09) years and 51 patients with CSU (male 33%) in the mean age of (SD) 35.8 (8.53) years were enrolled in this observational study. All the participants completed a Short-Form 36 (SF-36) QoL. Results: The QoL related to social functioning was significantly worse among CSU patients. There were differences related to gender found in the group of patients with T1DM—where men tended to declare a better quality of life than women (p = 0.015)—especially in the area of energy/fatigue and pain. It appeared that due to physical and emotional problems occurring in married patients, the QoL is lower in T1DM group in comparison to the CSU one. Conclusions: The patients with CSU presented significantly worse social functioning compared to the ones with T1DM. This fact proves the QoL impairment level is not always related to the level of health danger. The differences in the QoL related to gender and marital status found among T1DM patients point to the necessity for further exploration in a larger group of patients. Due to the fact that optimal disease management should ensure patient’s good emotional well-being, there is a need for additional psychological and social care for patients from those two groups.